Evolution : the origins and mechanisms of diversity - Bard, Jonathan (Boca Raton : CRC Press, 2022)
"Evolution is the single unifying principle of biology and core to everything in the life sciences. More than a century of work by scientists from across the biological spectrum has produced a detailed history of life across the phyla and explained the mechanisms by which new species form. This textbook is unique in describing both this history and the mechanisms of speciation at a level providing students the tools needed to read the research literature on evolution. Students will therefore learn about cladistics, molecular phylogenies, the molecular-genetical basis of evolutionary change including the important role of protein networks, symbionts and holobionts, together with the core principles of developmental biology. The book also includes introductory appendices that provide background knowledge on, for example, the diversity of life today, fossils, the geology of Earth and the history of evolutionary thought"--
includes Appendix, Glossary, References, Index
Keywords: Evolution (Biology) -- Human evolution -- Evidence for evolution -- Histroy of life